2020
DOI: 10.3390/jcm9030641
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Total Treatment Time in Patients Treated with Orthognathic Surgery Using the Surgery-First Approach: Multivariable Analysis Using 3D CT and Scanned Dental Casts

Abstract: The aim of this study was to analyze factors affecting treatment times in patients treated with the surgery-first approach (SFA) for orthognathic surgery. Fifty skeletal class III patients who had undergone SFA bimaxillary orthognathic surgery were enrolled. Retrospective chart reviews and analysis of 3D CT and digitally scanned casts were conducted to assess the total treatment time. Statistical analysis was then performed with multiple study variables. Longer treatment times were required for patients with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…59 Stable posterior occlusion, a minimum of three contact points, 62,63 no previous extractions, coordination of the maxillary and mandibular midlines, and presence of a limited crossbite (not more than one buccal cusp width of the maxillary molars) are essential prerequisites to achieve a stable occlusion and therefore skeletal bone healing in the ideally positioned maxilla and mandible. 60,64 In our third patient, multiple previous extractions, including molars, and only two contact points created a considerably unstable preoperative occlusion. Similar problems could have coexisted in other donors and this might explain, in part, the high percentage of malocclusion after transplantation.…”
Section: Discussionmentioning
confidence: 75%
“…59 Stable posterior occlusion, a minimum of three contact points, 62,63 no previous extractions, coordination of the maxillary and mandibular midlines, and presence of a limited crossbite (not more than one buccal cusp width of the maxillary molars) are essential prerequisites to achieve a stable occlusion and therefore skeletal bone healing in the ideally positioned maxilla and mandible. 60,64 In our third patient, multiple previous extractions, including molars, and only two contact points created a considerably unstable preoperative occlusion. Similar problems could have coexisted in other donors and this might explain, in part, the high percentage of malocclusion after transplantation.…”
Section: Discussionmentioning
confidence: 75%
“…The use of skeletal orthodontic anchorage is acknowledged to be effective in controlling movements of individual teeth, or groups of teeth-or in fact entire arches in certain surgical and non-surgical situations [1,5]. Three-dimensional imaging, planning and treatment technology will continue to be developed to the advantage of all those involved in all types of orthognathic treatment [2,18]. By all accounts, in skilled hands, Surgery-first has been shown to be an effective way in which various dentofacial problems can be managed [4].…”
Section: Discussionmentioning
confidence: 99%
“…The so-called Surgery-first approach (usually involving sophisticated three-dimensional digital planning and the use of skeletal screws and plates as orthodontic anchors for necessary tooth movements) has been promoted to reduce "exceptionallylong presurgical orthodontic treatment durations of two years or more" [1]. It is also promoted on the basis that the so-called Rapid Acceleratory Phenomenon (the RAP) effect) following bone trauma or surgery allows the teeth to move through bone more quickly-in the end, leading to much-reduced total active treatment durations [1,2]. It has been pointed out however that, despite the use of skeletal orthodontic anchorage, presenting dentoalveolar compensations may not always be completely reduced [3].…”
Section: Introductionmentioning
confidence: 99%
“…(Delgani, Fazeli & Sattarzadeh, 2017) Both studies considered a group of patients with different characteristics of malocclusion. Kim, J.-Y., et al (2020), established factors that affect treatment time in 50 class III patients, using three-dimensional computed tomography and scanned dental models of all patients. We selected 22 men and 28 women with a mean age of 22 years.…”
Section: Surgery-first Approach Vs Conventional Orthognathic Surgerymentioning
confidence: 99%
“…Several other comparative studies of cephalometric measurements have concluded that the instability factors in SFA are a very pronounced overjet, very deep curve of Spee, and a very severe negative overjet. (Kim et al, 2020;Ko et al, 2011;Jeong et al, 2017)…”
Section: Stability After Surgery-first Approachmentioning
confidence: 99%